Vilka möjligheter och hinder finns det för att skapa en och samma strategi för skyfall hantering, dagvattenhantering samt vattenrening i tätbebyggd stadsmiljö i Eslövs kommun? - Podric,Sasa (2025)
Due to rapid urbanization and industrialization, cities have been seen as one of the main contributors to climate change and its negative impacts in recent decades. Many of the Nordic countries have experienced an increased number of torrential rains and floods in recent years, resulting in both property and environmental damage as well as possible negative effects on the well-being of citizens. Eslövs municipality has experienced a heavy rainfall event and floods in winter 2024 and they decided that climate adaptation plan for the heavy rains and floods is necessary. Therefore, investigations on the technical measures, spatial possibilities and possible economic, legal, and organizational obstacles were carried out. The chosen method was semi-structured interviews that were carried out in municipalities that worked proactively or retroactively on the adaptation plans to downpour events. All interviewees stated more than one technical measure that they have implemented in their municipality to minimize the risks arising from flash floods. This led to the conclusion that multiple technical measures could potentially lead to more successful adaptation to the downpour events. The results also show that there are financial, legal, and organizational barriers that affect the implementation and implementation of sustainable stormwater management in interviewed municipalities. Most of the technical measures and strategies for managing stormwater runoff tend to be multifunctional, which indicates that they have a predisposition to fulfill multiple operations simultaneously. However, it cannot always be assumed that each function will be as efficient as possible if all features of the measure are not included in the planning and construction process.